Management of Phytophthora foot rot and nematode diseases in black pepper (Piper nigrum L.) - GANGADHARAPPA, M S LOKESH, P M (Journal of Spices and Aromatic Crops, 1995)
Phytophthora foot rot and nematode diseases of black pepper were managed effectively by following cultural practices; neem cake and phorate application; spraying, drenching and pasting of Bordeaux mixture (1%) before onset of monsoon and Akomin (0.04%) and Ridomil MZ - 72 WP (100 ppm) as spraying and drenching during second week of July and September, respectively, as second and third round application.